Saliva for COVID-19 Testing: Simple but Useless or an Undervalued Resource? - Pijuan-Galito, Sara; Tarantini, Francesco Saverio; Tomlin, Hannah; Jenkins, Harry; Thompson, Jamie Louise; Scales, Danielle; Stroud, Amy; Tellechea Lopez, Ana; Hassall, James; McTernan, Philip G.; Coultas, Andy; Arendt-Tranholm, Asta; et al. (Frontiers in Virology, 2021)
During the COVID-19 pandemic, countries with robust population-based asymptomatic testing were generally successful in controlling virus spread, hence reducing hospitalisations and deaths. This effectiveness inspired widespread asymptomatic surveillance for COVID-19/SARS-CoV-2 globally. Polarised vaccination programmes coupled with the relatively short-lived immunity vaccines provide mean that reciprocal cross-border exchanges of each new variant is likely, as evidenced by Delta and Gamma, and asymptomatic testing will be required for the foreseeable future. Reliance on nasopharyngeal swabs is contributing to ‘testing fatigue’ arising due to difficulties in standardising administration, unpleasantness and inappropriateness of use in younger people or individuals with special needs. There has also been erosion in confidence of testing due to variable and/or poor accuracy of lateral flow devices to detect COVID-19. Here, we question why saliva-based PCR assays are not being used more widely, given that standardisation is easy and this non-invasive test is suitable for everyone, providing high sensitivity and accuracy. We reflect on our experience with the University of Nottingham COVID-19 Asymptomatic Testing, where (as of October 2021) 96,317 samples have been processed by RT-qPCR from 23,740 repeat saliva donors, yielding 465 positive cases. We challenge myths that saliva is difficult to process, concluding it is an undervalued resource for both asymptomatic and symptomatic detection of SARS-CoV-2 genomes to an accuracy of >99% and a sensitivity of 1-10 viral copies/ml. In July 2021, our data enabled Nottingham to become the first UK University to gain recommended for accreditation and the first UK institute to gain this accolade for saliva.